Effect of Variations in the Pretreatment of Organic Waste on The Growth of Black Soldier Flies (BSF) Larval - Lili Mulyatna; Anni Rochaeni; Riana Saputra; Bryan Yogi; Ihsanul Fiqri (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
This study was conducted to see the effect of size and freshness variations of organic waste on BSF growth. The research was conducted on laboratory-scale research at campus of Pasundan University and field-scale research on Pojok Kang Pisman at Bandung City-hall. In laboratory-scale research, the organic waste used is artificial organic waste whose composition is close to organic waste from market. Meanwhile in field-scale research, the organic waste used is from market organic waste. Variations in pretreatment were carried out by varying the organic waste size and freshness in laboratory-scale research and comparison in order of chopping and fermentation of organic waste in various cocopeat thickness in field-scale research. Maggot/BSF growth analysis was carried out by calculating the waste reduction index, Efficiency of Conversion Digested Feed, survival rate, and maggot protein tests. The results of the laboratory study showed that the smaller the size of the waste influenced increasing the WRI, SR and ECD values but had little effect on the protein content of the larvae. The protein content of larvae is suitable for chicken feed (19-21%). However, when the waste was fermented, there was a significant increase in WRI and SR, and the protein content of the larvae increased (32-34%), suitable for tilapia and catfish feed. Field research results with higher larval density in fermented waste resulted in higher WRI and ECD values compared to laboratory results with lower larval density. In addition, the treatment of chop-fermentation and fermentation-chopped sequences gave different water content values ​​which affected the WRI and ECD values. The higher the water content, the lower the WRI and ECD values. The protein content of larvae in the field study was almost the same as in the laboratory study, ranging from (31-34%).